A Theory of Collective Bargaining - Hameed, Syed (Relations industrielles / Industrial Relations, 1970)
The author brings out the inadequacies of the present theoretical models in explaining collective bargaining and provides the constructs of a more complete and integrated body of theory. He also notes the importance of using functional terms in a theoretical model of this kind.